Bioinformatics Protocols in Glycomics and Glycoproteomics. Issue 1 (1st April 2014) - Tang, Haixu; Mayampurath, Anoop; Yu, Chuan‐Yih; Mechref, Yehia
Abstract: Glycomics aims to identify the whole set of functional glycans of glycoconjugates (attached to proteins or lipids) in biological samples. Glycoproteomics aims to characterize the complete structure of all glycoproteins in biological samples, including the glycosylation sites of proteins and the various glycan structures attached to each of these sites. Mass spectrometry (MS) and microarray are high‐throughput technologies that are commonly used in glycomics and glycoproteomics, which often result in the generation of large experimental datasets. Bioinformatics approaches play an essential role in automated analysis and interpretation of such data. This unit describes and discusses the computational tools currently available for these analyses, and their glycomics and glycoproteomics applications. Curr. Protoc. Protein Sci . 76:2.15.1‐2.15.7. © 2014 by John Wiley & Sons, Inc.